A parallel corpus-based study of the French verb tomber ‘to fall’: Its semantic plurivocity and equivalents in Polish and Lithuanian - Cholewa, Joanna; Valiukienė, Vita (Kalbotyra, 2022)
The analysis presented in this article is based on the trilingual parallel corpus CTLFR-PL-LT, composed of original French literary texts and their translations into Polish and Lithuanian. The undeniable usefulness of parallel corpora for studies in contrastive linguistics has already been established (Teubert 1996; Kraif 2011; Altenberg and Granger 2002 et al.). The corpora offer rich and reliable data, they [...] “allow us to see meaning through translation” (Johansson 2007, 57).The purpose of this study is twofold: we first aim to analyse the semantic plurivocity of the French verb tomber ‘to fall’ in literary texts. Secondly, we propose to examine the heterogeneity of the equivalents of tomber ‘to fall’ in Polish and Lithuanian, which will allow us to specify which strategies (verbal or other) are used to translate the meanings of the chosen verb. We also check whether the selected verbs in the Lithuanian and Polish translations express the same meaning element of tomber ‘to fall’. It will be particularly interesting to be able to observe whether strategies adopted by translators are specific to each of the target languages, genetically different, or common to both. Thus, we hope to contribute to contrastive French-Polish-Lithuanian research, which has so far been quite scare.
Keywords: trilingual parallel corpus (French-Polish-Lithuanian); tomber ‘to fall’; semantic plurivocity; Polish equivalents of tomber ‘to fall’; Lithuanian equivalents of tomber ‘to fall’